TINJAUAN YURIDIS PERTANGGUNGJAWABAN PIDANA TERHADAP DOKTER DAN RUMAH SAKIT TIDAK MEMBERIKAN INFORMED CONSENT KEPADA PASIEN DALAM HAL TERJADINYA KEMATIAN ATAU LUKA BAGI PASIEN - ', Nurhasannah; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The time of the examination the doctor in the hospital, patients have few rights, one of therights of patients who become problems in reality at the moment is the approval of a medicalaction (informed consent). In fact, the approval of the medical act is often denigrated by doctorsand their implementation is often not in accordance with the rules in the Act giving rise tomedical disputes. Consent to medical acts also created due to the therapeutic agreements whichgive rise to rights and obligations for both parties i.e. the doctor and the patient. Informedconsent or it can be a medical act approval of oral and written consent. It depends from the bigand the small risk of the surgery being performed. In the wake of a dispute between medicaldoctors with patients, the hospital also responsible. It is already regulated in Act No. 44 of theyear 2009 About the hospital article 46. Problems in writing how the criminal liability of doctorsand hospitals in case of errors and omissions in the exercise of medical practice. because it cancause disability. Either permanent disability or temporary disability and even cause death.The purpose of this research is to analyse the setting and the criminal liability of doctorsand hospitals do not provide informed consent in case of occurrence of death or injuries for thepatient research methods used in this thesis is the normative legal research, legal research thatis done by examining the references or secondary data, can be called a normative or legalresearch legal research library. This research uses the methodology of research on legalprinciples.The criminal liability of the doctor must see whether due to negligence or deliberateaction, criminal liability of hospitals only as in negligence, criminal liability and other healthworkers should be seen according pelimpahan authority of a doctor. We need a regulationregarding the criminal liability of doctors, hospitals and health workers. Besides the approval ofthe medical act must be run properly because it is the right of the patient, as well as theapplication of congruency should the law against criminal acts of malpractice.